2013
DOI: 10.1021/es4003795
|View full text |Cite
|
Sign up to set email alerts
|

Screening Houses for Vapor Intrusion Risks: A Multiple Regression Analysis Approach

Abstract: The migration of chlorinated volatile organic compounds from groundwater to indoor air-known as vapor intrusion-can be an important exposure pathway at hazardous waste sites. Because sampling indoor air at every potentially affected home is often logistically infeasible, screening tools are needed to help identify at-risk homes. Currently, the U.S. Environmental Protection Agency (EPA) uses a simple screening approach that employs a generic vapor "attenuation factor," the ratio of the indoor air pollutant conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…Thus it appears unlikely that the six orders of magnitude variation in source-to-subslab attenuation is attributable to temporal effects. Moreover, the effect of building construction differences is not nearly significant enough to induce such variation [14]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus it appears unlikely that the six orders of magnitude variation in source-to-subslab attenuation is attributable to temporal effects. Moreover, the effect of building construction differences is not nearly significant enough to induce such variation [14]. …”
Section: Resultsmentioning
confidence: 99%
“…This value is consistent with the maximum αgwss (0.4) from Figure 5, and the earlier derived αssin of 0.02. Johnston and Gibson [14] likewise showed that this value (0.004) would be conservative for most cases in EPA database, except for a few with shallow groundwater source, slab-on-grade construction on very coarse soil. The above analysis shows that the greater weakness in prediction of αgwin may be in the prediction of αgwss.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations